Developing a Principles-Based Framework to Link the Governance of Genomics Research and Biobanking in Africa to Global Health Justice - Munung, Nchangwi Syntia (Department of Medicine, 2020)
Background Genomics research has introduced significant transformations in the way health research is traditionally structured. Firstly, genomics research often requires long-term storage of biological samples for future unspecified uses. Secondly, the stored samples may be shared with researchers across the globe for the purposes of research. Thirdly, genomics researchers are increasingly required to make their research data publicly available for use by other researchers and institutions from around the world. Whilst data and sample sharing offers significant benefits for global health research, in Africa, it is taking place amidst a background of:structural inequities in health and health research between Africa and High Income Countries (HICs). There are also concerns around the exploitation of African researchers and study populations, mainly hinged on historical experiences in global health research, what has been termed scientific imperialism or “extractive” research. It is therefore not surprising that the rise in genomics research and biobanking studies in Africa has been accompanied by strong calls to address the ethical legal and social issues (ELSIs) raised by genomics research and biobanking in Africa. Some of these ELSIs focus on individual-level issues (micro-justice), others go beyond that to include broader societal ELSIs (macro-level justice) such as: secondary access to samples and data, benefit sharing, exploitation of African researchers and populations, intellectual property and the ownership of samples and data. One way of addressing these macro-level justice-related ELSIs is through governance.